Experimental and Numerical Study on Flame Inhibition Mechanism of Methane–Coal Dust Hybrid Explosion by Ultrafine Water Mist with Novel Chemical Additives - Li Liu; Yongheng Jing; Le Sun; Yao Tang (Fire)
Coal mining frequently sees explosions caused by methane/coal dust mixtures, resulting in significant harm to people and property damage. This study utilized the Hartmann pipe experiment to investigate the inhibition mechanisms of ultrafine water mist (UWM) containing phosphorus-based sodium inhibitors (sodium dihydrogen phosphate (NaH2PO4) and sodium phytate (C6H6Na12O24P6)) on methane/coal dust hybrid explosions. The results indicate that UWM containing NaH2PO4 and C6H6Na12O24P6 significantly reduces flame propagation velocity, flame height, and flame temperature, thereby effectively inhibiting the development of methane/coal dust hybrid explosion flames. UWM containing C6H6Na12O24P6 exhibited superior inhibition performance, reducing the flame temperature to 157.6 °C, the peak flame propagation velocity by 2.26 m/s, and the flame height by 5.66 mm. The inhibition mechanism of UWM containing phosphorus-based sodium inhibitors primarily involves physical heat absorption and chemical inhibition. The evaporation of UWM absorbs heat, thereby reducing the temperature in the reaction zone. Simultaneously, it generates a large amount of water vapor, which dilutes the fuel concentration per unit volume and reduces the collision frequency between fuel molecules and oxygen. The active free radicals (such as sodium oxygen radical (NaO), metaphosphoric acid (HPO2), HOPO (peroxyphosphate radical), etc.) produced by the decomposition of NaH2PO4 and C6H6Na12O24P6 react with free radicals (O, H, and OH), effectively reducing the concentration of free radicals, interrupting the chain reaction, and weakening the explosive severity. The decomposition products of the phosphorus-sodium components increase the heat capacity of the combustion products, dilute and isolate the combustion zone, and further reduce the explosive severity. These findings provide significant scientific and engineering support for the safe management of coal mines.